Teaching Democratic Humility to Improve Classroom Discussion - Kendall, Kason (Research in Social Sciences and Technology- OpenED Network, 2023)
Democratic discussion in the classroom has been viewed as a way to increase consensus, however the spread of false and misleading information through social media and influencers can make classroom discussions problematic. This electronic text analysis study highlights the social media site of Quora and posts related to the Gulf War. Posts related to the Gulf War is critically analyzed and their potential impacts are examined. This study also analyzes the posts and potential impacts of a conservative influencer named James Lindsay. It also analyzes specific polarizing posts that Lindsay has made on Instagram and highlight the potential impacts on classroom discussions of some of these posts. A purpose of the study is to analyze negative potential impacts of social media on student’s views and on classroom discussions. The study also highlights two potential solutions to overcoming these negative potential impacts. One solution is to use Stanford History Education Group’s Civic Online Reasoning, and another solution is to explicitly teach Democratic humility. With democratic humility, individuals learn not to make hyperbolic claims about their beliefs. Students could also be taught when learning about democratic humility, the importance of suspending judgement until they have gathered sufficient information on the topic.